Familial factors associated with development of alcohol and mental health comorbidity - Salom, C.; Williams, G.; Najman, J.; Alati, Rosa (Wiley-Blackwell Publishing Ltd., 2015)
© 2014 Society for the Study of Addiction. Background and Aims: Co-occurring mental health and alcohol problems appear to be associated with greater health burdens than either single disorder. This study compares familial and individual contributions to development of comorbid alcohol/mental problems and tests whether these differ from single disorders. Design: Women (n=6703) were recruited during pregnancy to the longitudinal Mater-University of Queensland Study of Pregnancy (MUSP). Mother/offspring dyads were followed over 21 years. Setting: Mater-Misericordiae Public Hospital, Brisbane, Australia. Participants: Primary offspring from the MUSP with full psychiatric information at 21 years and maternal information at age 14 (n=1755). Measurements: Structured interviews at age 21 yielded a four-category outcome using mental health and alcohol modules of the Composite International Diagnostic Interview (no disorder, alcohol only, mental health only and comorbid alcohol/mental health). Multinomial logistic regression models were adjusted for gender, maternal mental health and substance use, family environment and adolescent behaviour. Findings: Maternal smoking [odds ratio (OR)=1.56; 95% confidence interval (CI)=1.09-2.22 versus no-disorder] and low mother-offspring warmth (OR=3.19; 95% CI=1.99-5.13) were associated with mental health/alcohol comorbidity in young adults, as were adolescent drinking (OR=2.22; 95% CI=1.25-3.96), smoking (OR=2.24; 95% CI=1.33-3.77) and attention/thought problems (OR=2.04; 95% CI=1.18-3.52). Some differences were seen from single disorders. In a subsample with paternal data, fathers' drinking problems (OR=2.41; 95% CI=1.10-5.29) were more associated strongly with offspring mental health/alcohol comorbidity than both single disorders (P<0.05). Conclusions: Maternal smoking and low mother-child warmth appear to be related to alcohol, mental health and comorbid disorders at age 21, possibly via constituent alcohol and mental health disorders. Adolescent drinking and attention/thought problems appear to be associated with comorbid disorders but not with individual alcohol and mental health disorders.